Kelayakan Bisnis Percetakan Syailendra Kota Palangkaraya Ditinjau Dari Aspek Pemasaran (International Forum of Researchers and Lecturers, 2024)
This study was conducted to determine whether a printing business should be established in Palangkaraya. The data sampled in this study is qualitative primary data. The collection of all data required in this study was carried out through the interview method. According to Esterberg in Sugiyono (2020:114) an interview is a meeting of two people to exchange information and ideas through questions and answers, so that meaning can be contributed to a particular topic